Inclusão e permanência de servidores com deficiência na UFSM: propostas de ações de acessibilidade - Wagner, Giseli Rodrigues (2019)
The entry of persons with disabilities into the labor market is ensured by law. However, only allowing the vacancy does not guarantee the full inclusion and permanence of these people in the workplace. It is necessary that organizations be prepared and have in their culture the practice of accessibility actions that contribute to this process. In this sense, the present study aimed to propose suggestions for accessibility actions to expand the inclusion and permanence of servers with desability in UFSM. For this purpose, a survey was carried out with 26 disabled UFSM servers, 14 immediate boss of these servers, one representative of PROGEP and one of the Accessibility Core, in order to understand the perspectives of accessibility in the Institution. The study was characterized as quali-quantitative, with exploratory character of case study. In the data collection, for all the participants, questionnaires with essay questions were used in order to outline the current panorama of the actions of accessibility, inclusion and permanence in UFSM. In addition, the questionnaires of Quality of Life at Work (CARVALHO-FREITAS, 2007) and the Satisfaction and Attitudes Scale (GUERREIRO; ALMEIDA; SILVA-FILHO, 2014) were applied to disabled servers and the Inventory of Disability Concepts in Work Situations and Inventory of Actions for Adequacy of Working Conditions and Practices (CARVALHO-FREITAS, 2007) for the immediate boss. The results indicate that UFSM is on the way to building an accessible University, but still needs actions that can help in the inclusion and permanence of its disabled servers. Thus, actions were suggested in the 6 dimensions of accessibility proposed by Sassaki (2010), with recommendations in the architectural, attitudinal, communicational, instrumental, methodological and programmatic dimensions., such as mapping of the adaptation needs of the buildings in the Campus, actions of sensitization of the academic community , write documents in accessible formats, have adapted instruments and materials, qualify professionals to work on the subject of the disabilities, comply with the laws that support the disabled people, among others.